The adaptation of IMC principles to local small retail businesses for their own use. - Goh, Cheng Cheng. (2009)
This research paper presents an analysis of how the principles and tools of Integrated Marketing Communications (IMC) can be adapted for use by the local small retail businesses in Singapore. It first introduces the reader to how IMC evolved and its definition. IMC begins with having an understanding of the Consumer Decision Making Process. From here, the role and implications of marketing communications are derived. In addition, the paper also talks about the various IMC tools that can be used and examines their strengths and limitations. Based on this, the principles of IMC are adapted for the use by the local small retail businesses. Several low cost IMC tactics are also suggested for these small businesses. The paper then concludes with an actual case study on how this may be applied to a local small retail gift shop.